Culinary Tourism Development Strategy In Sukabumi - Nurmilah, Risma; Ade Sudarma; Alhidayatullah, Alhidayatullah (International Journal of Entrepreneurship and Business Management, 2022)
Culinary tourism is an essential basis for assessing the regional creative economy. The main purpose of this study is to determine the development strategy of culinary tourism in Sukabumi. The method used is a SWOT analysis.The culinary tourism development plan begins by looking at the business characteristic and identified culinary problems so that the concept of culinary tourism development appears based on the strengths, weaknesses, opportunities and threats. The results of this analysis, there are similarities in main characteristics and problems that emerges from every culinary entrepreneur. Similarities in goals and directions impacton the similarities of strategy in its development. This research resulted in three stages strategy namelyshort-, medium- and long-term strategy. Promotion and revitalization culinary place are proposed inshort term strategy.In addition, medium term strategy proposes development of human resources while long term strategy propose government policiesin tourism development. The future plans in culinary tourism development should be ina consistent coordination framework so that results positive regional economic growth.